2019
DOI: 10.1016/j.heliyon.2019.e01223
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal interactions between cancer and Schwann cells contribute to oral cancer progression and pain

Abstract: Pain associated with oral squamous cell carcinoma (oral SCC) decreases quality of life and survival. The interaction between cancer and the peripheral nerves is known to initiate and amplify pain and contribute to carcinogenesis. Schwann cells envelop peripheral nerves and are activated in response to neuronal damage. The contributions of Schwann cells to oral SCC progression and pain are unknown. Using a non-contact co-culture model, we demonstrate that Schwann cells (RSC-96) and oral SCC cells (HSC-3) recipr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 59 publications
(105 reference statements)
1
34
0
Order By: Relevance
“…We have previously demonstrated that rat Schwann cells (RSC-96) and human oral SCC cells (HSC-3) reciprocally interact to promote proliferation, migration, and invasion 11 . Here we found that human Schwann cells increased migration and proliferation in the presence of human oral cancer cells as well; the growth rate of human Schwann cells was increased in the presence of either precancer dysplastic oral keratinocytes (DOK) or HSC-3 cells grown in culture inserts ( P < 0.001, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously demonstrated that rat Schwann cells (RSC-96) and human oral SCC cells (HSC-3) reciprocally interact to promote proliferation, migration, and invasion 11 . Here we found that human Schwann cells increased migration and proliferation in the presence of human oral cancer cells as well; the growth rate of human Schwann cells was increased in the presence of either precancer dysplastic oral keratinocytes (DOK) or HSC-3 cells grown in culture inserts ( P < 0.001, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Blocking JNK that is upstream of c-Jun activation 61 is also effective in pain relief in our mouse paw xenograft model. Cancer- or hypoxia-activated Schwann cells release nociceptive mediators such as IL-6, TNFα, CXCL2, and IL-8 11 , 15 ; these mediators could sensitize primary afferent neurons to cause pain. Schwann cell activation causes myelin breakdown 41 ; the loss of structural support and insulation by myelin sheath breakdown is another possible explanation of pain produced by activated Schwann cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations